Readmission Events Among Patients Who Received ACT Services as Pillar I of SIRUKOGALAR at Mutiara Sukma Mental Hospital - Lindawati Lindawati; Fauzi Tsanifiandi; ACT Team ACT Team (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2022)
Readmission can occur in all diseases, including in patients with mental disorders where the sufferer experiences problems in the ability to judge reality or which one bad. One of the factors that cause recurrence in patients with mental disorders high emotional level. Another factor is the ability of patients to distinguish between family and hospital staff. In this case, most mental patients are more afraid of hospital staff than their families, so that when patients are allowed to go home the patient no longer follows directions from the family and feels that there is nothing to be afraid of. This caused the patient become not routinely monitored, and prone to experience a relapse. As the first pillar of "SIRUKOGALAR" (Three Communication Pillars Referral System) at Mutiara Sukma Mental Hospital, ACT (Assertive Community Treatment) was used as a comprehensive client-centered mental health program that. This program was carried out to reduce hospitalization, improve the patients’ quality of life, train abilities in fulfilling daily activities, provide support to families and caregivers, reduce symptoms of disability and handle crisis in the community. This study aims to describe the incidence of readmission in patients who get ACT service at the the Mental Health Hospital in 2022. This study is a retrospective study. The data of patients were collected from the medical record from January 2020 to June 2022. The study results show that there is a decrease in the trend of readmission among patients who get ACT services in 2020